Strategi Man 1 Medan Dalam Memberikan Bimbingan dan Karir Guru - Pratama, Ahmad Yudha; Kahfy, Ashabi; Dalimunthe, Gilang Luthfie; Rambe, Sutan Rizki (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explore the career development and guidance strategies of teachers at MAN 1 Medan, which play an important role in improving the quality of education. A qualitative descriptive approach was used to explore the challenges and opportunities for teacher career development, with data collected through interviews, observations, and documentation. The findings indicate that MAN 1 Medan faces limitations in internal training programs, psychological support, and evaluation and supervision of guidance programs. Recommendations include developing internal career training programs, increasing access to training from the Ministry of Religious Affairs, and strengthening teacher discussion forums. These strategies are expected to improve teacher professionalism, teaching quality, and teacher job satisfaction at MAN 1 Medan